E-Learning Implementation Analysis: Reviewing the Evolution, Challenges, and Contribution of Strategic Thinking to Optimization in Higher Education - Imam Fatah Santoso (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
E-learning has undergone significant evolution, transforming from a CBT-based system to a Hybrid Learning model integrated with ICT technology, making it a primary solution to overcome the barriers of space and time. This study aims to analyze the historical development of e-learning, review comparative implementations, and identify its strategic roles, advantages, and challenges, in order to formulate optimization strategies in higher education. The method used is a qualitative, descriptive-analytical approach through literature review and content analysis. The analysis shows that e-learning is crucial in providing flexibility and expanding access to learning resources, while simultaneously encouraging learning autonomy. However, successful implementation depends heavily on efforts to address the Digital Divide, reduce digital fatigue, and foster social presence to combat isolation. In conclusion, to maximize the potential of e-learning, institutions must focus on developing bandwidth-efficient platforms, training faculty as Instructional Designers, and adopting a scalable Hybrid Learning model to ensure Digital Equity and improve student learning outcomes.